George Deacon and the circulation of homeopathic therapies in Lima (1880-1915) - Patricia Palma (História, Ciências, Saúde: Manguinhos)
Abstract Homeopathy arrived from the United States to Peruvian soil in the last decades of the nineteenth century, broadening the repertoire of existing medical knowledge, which included an emerging medical profession, Chinese herbalists, and indigenous practitioners. This article examines the circulation and use of homeopathic therapies and medicines in Lima from the time when the American homeopath George Deacon initiated his practice, in the 1880s, until his death, in 1915. Although homeopathy was not the most widely used medical therapy in the country, it nevertheless posed a threat to professional medicine and the School of Medicine’s desired monopoly of the field of medicine.